Effect of effective microorganism for the recycling of crop wastes and dry land weeds - Balaji, T; Manikandan, K; Arunkumar, V; Ananthi, K; Rajesh, M; Vijayakumar, M; Sanjivkumar, V (Plant Science Today, 2025)
The study, conducted during 2015-16, aimed to evaluate the effectiveness of pit and bed methods in composting selected crop residues and weed biomass. The waste materials, viz., coconut leaf stalk with leaflets, mixed crop residues, mixed dryland weeds, banana plant and kapok seed pod without cotton were chosen based on their local availability, decomposition potential and nutrient content. Ten treatments were tested, incorporating 50 kg of cow dung and 500 g of urea per ton of waste, with and without effective microorganisms at 1 liter per ton. The composting process was monitored for temperature variations, nitrogen content, carbon content and decomposition efficiency. Composting efficiency was influenced by factors such as the nature of crop residue, C:N ratio, moisture, temperature and aeration. Results indicated that the bed method facilitated faster decomposition than the pit method, primarily due to improved aeration, which enhanced microbial activity. Treatments with Efficient Microorganisms (EM) showed accelerated decomposition and better compost. The findings emphasize the importance of selecting appropriate composting techniques based on residue characteristics. Efficient composting not only transforms crop residues into nutrient-rich compost but also improves soil quality, contributing to sustainable agricultural practices. This study provides insights into optimizing composting methods for effective crop residue management.